2005
DOI: 10.1055/s-2005-864213
|View full text |Cite
|
Sign up to set email alerts
|

Early Language Growth in Children Adopted from China: Preliminary Normative Data

Abstract: Normative data on English language development in children adopted from China are needed to determine whether a child's language skills are within normal limits or significantly delayed relative to his or her peers who are other children adopted from China. A longitudinal survey of children adopted from China, modified from a similar survey used by Glennen and Masters (American Journal of Speech-Language Pathology 2002;11:417-433) with children adopted from Eastern Europe, was used to collect information on En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 7 publications
4
22
0
1
Order By: Relevance
“…The background questionnaire was based on one used by Glennen and Masters (2002) and Pollock (2005). It asked about the child's history and health, their level of proficiency in their birth language, their adoptive family, their current use of English and their native language, and their current language environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The background questionnaire was based on one used by Glennen and Masters (2002) and Pollock (2005). It asked about the child's history and health, their level of proficiency in their birth language, their adoptive family, their current use of English and their native language, and their current language environment.…”
Section: Methodsmentioning
confidence: 99%
“…But we know almost nothing about how they get there. While a number of researchers have studied language development in children adopted as infants or toddlers (see e.g., Glennen & Masters, 2002;Roberts, Pollock, Krakow, Price, Fulmer & Wang, 2005;Pollock, 2005), there is little work on acquisition in children who were adopted after 30 months.…”
mentioning
confidence: 99%
“…In general, the language of typical IA children catches up with their non-adopted peers by ages 3-4 years and continues to develop at a normal rate throughout their school-age years (Glennen & Bright, 2005). Pollock (2005) found that IA children, regardless of country of origin, acquired their first 50 words at a relatively matched pace. Measuring vocabulary every 6 months, she found steady vocabulary growth among IA children, which is initially somewhat slow for younger children but expands rapidly around 9-12 months post adoption.…”
Section: Language Contentmentioning
confidence: 96%
“…While their presence adds welcome variety to our already diverse classrooms and childcare centers, it also serves as a distinctive clinical dilemma for the early childhood professionals who care for them. Consider the following parent questions as illustrated by Pollock (2005):…”
mentioning
confidence: 99%
“…However, when the children's language skills were compared to English language expectations, the toddlers were further behind for their age than the infants were, indicating that the toddlers had further to go to catch up. Similarly, in a much larger longitudinal survey study of 141 children adopted from China between the ages of 7 and 43 months, Pollock (2005) found that children adopted at older ages produced more words and longer sentences in the first years after adoption than children adopted at younger ages; however, the older children lagged further behind English language norms.…”
Section: Introductionmentioning
confidence: 99%